Implementasi Ekonomi Terhadap Pajak Islam Dan Pajak Negara (Studi Kasus Mantan Pegawai DJP Pajak di Indonesia) - Rahmawati, Nur Rahma (ITB AAS INDONESIA Surakarta, 2024)
This article is about the function and purpose of creating mandatory tax regulations for all components of society. Islamic taxes taught by the Prophet Muhammad SAW have different provisions and types, thus providing us with knowledge to know how the differences are between what religion teaches and this era regarding state levies. The purpose of this article is to explain taxes according to the State and Islam, which looks at the case study of the Directorate General of Taxes in Indonesia from an economic perspective. The research uses a literary method that refers to a collection of real facts, both through written and visual documentation. This research produces a comparison of concepts or ways of understanding theories from time to time and aspects that trigger violations.